Effect of Pterygium on Corneal Endothelial Cell Count - يوسف, حبيب (Latakia University Journal -Medical Sciences Series, 2020)
Aim: to study the effect of pterygium on corneal endothelial cells in patients with unilateral pterygium. Methods: 26 patients with unilateral nasal pterygium were studied between june 2018 and july 2019, endothelial cells were studied in both eyes, and the normal eye was considered as control. And the relation between the ratio of pterygium to cornea and endothelial cell loss was studied. Results: ratio of pterygium to cornea was between 10% to 55% with a mean of 22%, and the difference in endothelial cell count between pterygium eye and control eye was between +8.9% to 35.2% with a mean of -11.4%. pearson coefficient showed significant relation between pterygium size and endothelial cell count decrease (R=0.645, p<0.001). Conclusion: the pterygium cause significant endothelial cell loss, and that should be considered when performing surgery.